Shuttle IoT: UTAR bus management system - Chin Pei Shan, Chin Pei Shan (2024)
Addressing the inefficiencies of bus wait times for UTAR students, this project introduces a real-time bus location tracking system with the function of calculate number of remaining seats, integrating IoT technologies within a Rapid Application Development (RAD) framework. The prototype includes a Raspberry Pi 4 paired with a Neo-M6 GPS HAT with Antenna and 5MP camera module. The GPS module utilizes satellite communication channel to pinpoint geographical coordinates. And the camera module utilizes WebSocket to stream video to AWS EC2 for processing. These coordinates and processing result stored within Firebase's Realtime Database for efficient data handling and retrieval. The system leverages Google Maps API, acquired through Google Cloud services, to render the positional data onto a map within a custom-built Flutter application. This setup ensures that the Raspberry Pi 4 on the bus provides real-time updates on both its location and the number of remaining seats. Consequently, UTAR students are empowered to monitor bus locations via the application in real-time, significantly optimizing their time management by diminishing periods spent waiting for transportation.